Pengalaman Perawat Pelaksana Dalam Menerapkan Keselamatan Pasien Di Rumah Sakit Dr. Bratanata Tahun 2022 - Nurfajrindah Nurfajrindah; Yusnilawati Yusnilawati; Suryadi Imran (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Health services in hospitals must be able to manage risks to patients and have the ability to learn how to follow up on incidents or injuries that occur and be able to implement solutions to reduce the risk of patient safety incidents occurring. Therefore, through hospital accreditation, service quality must be carried out in accordance with predetermined patient safety standards. This study aims to determine the experience of implementing nurses in carrying out patient safety at dr. Bratanata in 2022.